Epigenetics and Beyond: Targeting Histone Methylation to Treat Type 2 Diabetes Mellitus - Yang, Yang; Luan, Ying; Feng, Qi; Chen, Xing; Qin, Bo; Ren, Kai-Di; Luan, Yi (Frontiers in Pharmacology, 2022)
Diabetes mellitus is a global public health challenge with high morbidity. Type 2 diabetes mellitus (T2DM) accounts for 90% of the global prevalence of diabetes. T2DM is featured by a combination of defective insulin secretion by pancreatic β-cells and the inability of insulin-sensitive tissues to respond appropriately to insulin. However, the pathogenesis of this disease is complicated by genetic and environmental factors, which needs further study. Numerous studies have demonstrated an epigenetic influence on the course of this disease via altering the expression of downstream diabetes-related proteins. Further studies in the field of epigenetics can help to elucidate the mechanisms and identify appropriate treatments. Histone methylation is defined as a common histone mark by adding a methyl group (-CH3) onto a lysine or arginine residue, which can alter the expression of downstream proteins and affect cellular processes. Thus, in tthis study will discuss types and functions of histone methylation and its role in T2DM wilsed. We will review the involvement of histone methyltransferases and histone demethylases in the progression of T2DM and analyze epigenetic-based therapies. We will also discuss the potential application of histone methylation modification as targets for the treatment of T2DM.